Meridian Crossings : Hermit V. - Metamedia Symposium. - Vojtechovsky, Milos (Plasy : Hermit Foundation / Center for Metamedia Plasy, 1995)
Küntzel, Tilman ; Schulte-Steinberg, Anke ; Koivisto, Kaisu ; Matthews, Patrick ; Mackeeman, Christopher ; Moust, Alexander ; Best, Anna ; Goro, Hama ; Titlova, Margita ; Silver ; Cecchinni, Andrea Crociani & Loris ; Cernicky, Jiri ; Sedlácková, Sarka ; Dickson, John ; Crowson, Catherine ; Renwick, Arthur ; Snepp, Daniela ; Walter, Kathryn Miya ; Streicher, Max ; Fernandes, Michael ; Miller, David ; Richard, Thomas ; Eilat, Abraham ; Hnizdil, Ales ; Durham, Jimmie ; van Buuren, Ad ; Zet, Martin ; Paivio, Suzanne Miller & Alan ; MacLennan, Alistair ; Reardon, John ; Janicek, Martin ; Lagopulos, Athanasios ; Svoboda, Jan ; Via, Via
Tsjechisch
Metamedia Symposium: Meridian Crossings, Plasy Monastery, 23.06.1995 - 03.07.1995
Engels
boek